Virtual Dance Communities and the Right to the Internet - Krisel, Rebecca (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2022)
The COVID-19 global pandemic forced most nightlife venues to shut their doors in March 2020, leading to a loss of employment for nighttime employees and freelancers as well as a loss of revenue for the city. As night clubs shut down, the social dancers who fuel this part of the nightlife economy lost access to the spaces where they dance with others who share their musical tastes. Yet seedlings can spring up even in burned over territory. In the face of these pandemic challenges, the dance music scene reinvented itself, shifting from existing in-person to entirely virtual performance. This reimagination of nightlife points to a key element in the resilience of night-time social dancing: community. These virtual dance parties stemmed from, and perpetuated dance communities that replaced, and in some cases redefined, the experiences that dance communities formerly enjoyed in in-person venues. This paper explores this world of virtual dancing. Through conversations with venue owners, performers, and social dancers, as well as through a digital ethnography of virtual dance parties and their corresponding social media pages, this study asks whether and how virtual dance parties replicate the sense of community experienced in in-person dance parties and interrogates what the advent of virtual dance parties means for the future of urban nightlife. Building on the idea that social dancing is a right to the city (Krisel 2020; see also Harvey 2008; Lefebvre 1996), this study also explores how social dancing may also be a right to the internet and explores the parallel between the urban and internet environments as venues where subcultures can form communities and co-create both physical and virtual spaces.